PROFIL ASESMEN BUATAN GURU BIOLOGI SMA SASARAN KURIKULUM 2013 - KARTIKA DEWI, NOFIKA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
This research aimed to describe Biology teacher’s authentic assessment and test profile. The kind of this research was descriptive with qualitative approach. The subject of this research was Biology teacher of 10th grade Senior High School in Ponorogo Regency that have been implementing Kurikulum 2013. The primary source of this research was the teacher’s lesson plan and the secondary source was the responses in teacher’s questionnaire. The data collecting techniques used in this reasearch were questionnaire and documentation. The data analysis was descriptive percentage. Based on the data analysis are known that component suitability of authentic assessment were 29.59% indicator-task-rubric, 57.59% indicator-task, 4.83% task-rubric, and 7.25% only consist of task. 53.05% test had suitable with the indicator while 46.95% had not suitable. Keywords: assessment, Kurikulum 2013.